In situ detection of PR3-ANCA+ B cells and alterations in the variable region of immunoglobulin genes support a role of inflamed tissue in the emergence of auto-reactivity in granulomatosis with polyangiitis. (September 2018) - Weppner, Gesche; Ohlei, Olena; Hammers, Christoph M.; Holl-Ulrich, Konstanze; Voswinkel, Jan; Bischof, Julia; Hasselbacher, Katrin; Riemekasten, Gabriela; Lamprecht, Peter; Ibrahim, Saleh; Iking-Konert, Christof; Recke, Andreas; et al.
Abstract: Circulating anti-neutrophilic cytoplasmic autoantibodies targeting proteinase 3 (PR3-ANCA) are a diagnostic and pathogenic hallmark of granulomatosis with polyangiitis (GPA). It is, however, incompletely understood if inflamed tissue supports presence or emergence of PR3-ANCA + B cells. In search of such cells in inflamed tissue of GPA, immunofluorescence staining for IgG and a common PR3-ANCA idiotype (5/7 Id) was undertaken. Few 5/7 Id + /IgG + B cells were detected in respiratory and kidney tissue of GPA. To gain more insight into surrogate markers possibly indicative of an anti-PR3-response, a meta-analysis comprising IGVH and IGVL genes derived from respiratory tract tissue of GPA (231 clones) was performed. Next generation sequencing-based IGHV genes derived from peripheral blood of healthy donors (244.353 clones) and previously published IGLV genes (148 clones) served as controls. Additionally, Ig genes of three murine and five known human monoclonal anti-PR3 antibodies were analyzed. Primary and probably secondary rearrangements led to altered VDJ usage and an extended complementarity determining region 3 (CDR3) of IGHV clones from GPA tissue. Selection against amino acid exchanges was prominent in the framework region of IGHV clones from GPA tissue. The comparison of V(D)J rearrangements and deduced amino acid sequences of the CDR3 yielded no identities and few similarities between clones derived from respiratory tissue of GPA and anti-PR3 antibodies, arguing against a presence of B cells that carry PR3-ANCA-prone Ig genes among the clones. In line with the scarcity of 5/7 Id + B lymphocytes in GPA tissue, the results suggest that with respect to a local anti-PR3 response, methods detecting rare clones are required. Highlights: PR3-ANCA + B cells are present in inflamed tissue of granulomatosis with polyangiitis. Inflamed tissue-derived immunoglobulin genes carry signs of primary rearrangement. Inflamed tissue-derived immunoglobulin genes carry signs of secondary rearrangement. High-throughput approaches seem necessary to detect PR3-ANCA + B cells in situ . Monoclonal anti-PR3 antibodies vary in their antigen-binding region.